An epigraphic reanalysis of two stelae from First Intermediate Period Dendera in the Cairo Museum - Musacchio, Tracy (2006)
Fil: Musacchio, Tracy. University of Pennsylvania,. Department of Near Eastern Language and Civilizations; Estados Unidos